Dynamic visualisation of municipal waste management performance in the EU using Ternary Diagram method. (March 2017) - Pomberger, R.; Sarc, R.; Lorber, K.E.
Highlights: Three types of visualization for MWM perf.: positioning, dynamics and development. Eurostat table-form data of all 28 member states of the EU has been visualised. "Multi-speed" EU may be devided in: Recovery, Transition and Landfilling Countries. Dynamic visualisation of MWM perf. for the EU 28, Austria, Germany, UK and SK. Linked development of recycling & composting (60–65%) with incineration (40–35%). Abstract: This contribution describes the dynamic visualisation of European (EU 28) municipal waste management performance, using the Ternary Diagram Method. Municipal waste management performance depends primarily on three treatment categories: recycling & composting, incineration and landfilling. The framework of current municipal waste management including recycling targets, etc. is given by the Waste Framework Directive – 2008/98/EC. The proposed Circular Economy Package should stimulate Europe's transition towards more sustainable resources and energy oriented waste management. The Package also includes a revised legislative proposal on waste that sets ambitious recycling rates for municipal waste for 2025 (60%) and 2030 (65%). Additionally, the new calculation method for monitoring the attainment of the targets should be applied. In 2014, ca. 240 million tonnes of municipal waste were generated in the EU. While in 1995, 17% were recycled and composted, 14% incinerated and 64% landfilled, in 2014 ca. 71% were recovered but 28% landfilled only. Considering the treatment performance of the individual EU member states, the EU 28 can be divided into three groups, namely: "Recovery Countries", "Transition Countries" and "Landfilling Countries". Using Ternary Diagram Method, three types of visualization for the municipal waste management performance have been investigated and extensively described. Therefore, for better understanding of municipal waste management performance in the last 20 years, dynamic visualisation of the Eurostat table-form data on all 28 member states of the EU has been carried out in three different ways: 1. "Performance Positioning" of waste management unit(s) at a specific date; 2. "Performance dynamics" over a certain time period and; 3. "Performance development" expressed as a track(s). Results obtained show that the Ternary Diagram Method is very well suited to be used for better understanding of past developments and coherences, for monitoring of current situations and prognosis of future paths. One of the interesting coherences shown by the method is the linked development of recycling & composting (60–65%) with incineration (40–35%) performance over the last 20 years in the EU 28.